THE INFLUENCE OF IONIZING RADIATION ON THE THERMOPHYSICAL PROPERTIES OF MEAT FROM THE BROILER CHICKENS WITH DIFFERENT STRESS RESISTANCE - Roza T. Timakova; Sergey L. Tikhonov; Natal’ya V. Tikhonova; Sergey V. Shikhalev; Leonid S. Kudryashov (Теория и практика переработки мяса)
The studies on the influence of radiation treatment of carcasses from the stress-resistant and stress-sensitive broiler chickens on the thermophysical properties of raw meat are presented. An increase in thermal diffusivity of meat from the stress-resistant poultry by 24.7 % and 54.7 % after radiation treatment of carcasses with ionizing radiation doses of 9 kGy and 12 kGy, respectively, was established. In meat from the stress-sensitive poultry, this figure increased by 33.3 % and 35.8 % compared to the untreated carcasses.It is shown that radiation treatment of carcasses by applied doses increased the thermal conductivity coefficient of meat from the stressresistant poultry by 5.3% and 7.0 %; in meat from the stress-sensitive poultry, this figure increased by 2.0 and 6.2 times compared to meat from the carcasses not exposed to radiation. At the same time, the value of the heat capacity coefficient was reduced. The irradiated poultry meat samples accumulate energy of ionizing radiation more intensively, which allows the intensification of the thermal processes occurring at various stages of meat product production. Treatment of meat from the stress-resistant poultry with ionizing radiation can reduce the amount of meat with non-traditional autolysis due to changes in its functionaltechnological properties. The results of the research should be taken into account in technological processes in the production of meat products with non-traditional autolysis.